The The Necessity and Suggestion of Continuing Education for Accountants - Chen, Qiong Zi (Pacific International Journal, 2023)
Whether it is a government unit or an enterprise, in the process of carrying out daily accounting work, accountants are always the core of accounting work, and the quality of accountants is the necessary basic condition for accountants to engage in accounting work. It determines the quality of accounting work. Continuing education for accountants is to improve the overall quality of accountants, specifically including political literacy, professional ethics, and professional skills, so as to create a group of accounting personnel who meet the needs of social and economic development and are proficient in professional skills. Senior accounting management talents with high professional ethics. The content of continuing education for accountants is divided into public subjects and professional subjects. Public subjects include basic knowledge such as laws and regulations, policy theories, professional ethics, and technical information that professional technicians should generally master. Professional subjects are divided into professional general knowledge, professional There are three categories of core knowledge and professional development knowledge. This paper mainly combines the results of literature research on continuing education, and on the basis of previous studies, expounds the necessity of continuing education for accountants, analyzes the problems in the development of continuing education for accountants, and explores the future of continuing education for accountants. Development proposals and methods for readers’ reference.